PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. DAJIN SAUDARA INDONESIA CIREBON - Eman Sulaiman; Faisal Akbar; Nisaun Naziyyah (FEB Institut Bakti Nusantara, 2021)
This study intends to determine the effect of motivation and work environment on employee productivity at PT. Dajin Indonesian Brothers Cirebon. This type of research uses a quantitative descriptive approach with multiple regression analysis techniques. The type of data used is primary data obtained through surveys and observations using SPSS for Windows version 24. Secondary data is obtained from company data and from several books and journals that can be accounted for. The sample for this study was 74 respondents who took a probability sample using the Slovin formula. The results of the study based on the coefficient of determination showed that the level of influence of motivation (X1) on work productivity (Y) was 59.7%. The size of the influence of the work environment (X2) on work productivity (Y) based on the coefficient of determination of 74.4%. The effect of motivation (X1) and work environment (X2) on work productivity (Y) is 76.2%. In other words, productivity (Y) is influenced by motivation (X1). The work environment (X2) is 76.2%. The remaining 23.8% is influenced by other factors not included in this survey.